2009
DOI: 10.1073/pnas.0807596106
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive nanoscale columnar transistors

Abstract: This study reports a general methodology for making stable high-performance photosensitive field effect transistors (FET) from self-assembled columns of polycyclic aromatic hydrocarbons by using single-walled carbon nanotubes (SWNTs) as point contacts. In particular, the molecules used in this work are liquid crystalline materials of tetra(dodecyloxy)hexabenzocoronenes (HBCs) that are able to self-organize into columnar nanostructures with a diameter similar to that of SWNTs and then form nanoscale columnar tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 38 publications
2
81
0
1
Order By: Relevance
“…We tested a total of five devices and found that the modulation of conductivity with light was reproducible. Although the performance of these photoresponsive transistors [17] has not been optimized, the photoresponsive properties of the nanosheets are promising for organometallic-based optoelectronics. No charge accumulation in the initial several seconds was observed.…”
Section: ···Ptmentioning
confidence: 99%
“…We tested a total of five devices and found that the modulation of conductivity with light was reproducible. Although the performance of these photoresponsive transistors [17] has not been optimized, the photoresponsive properties of the nanosheets are promising for organometallic-based optoelectronics. No charge accumulation in the initial several seconds was observed.…”
Section: ···Ptmentioning
confidence: 99%
“…We have demonstrated that SWCNTs can function as efficient point contacts for nanoscale FETs. We made FETs out of both monolayers [54] and self-assembled columns [80] of polycyclic aromatic hydrocarbons. These devices are ultrasensitive to their chemical environment, temperature, and light.…”
Section: Ofets Based On Swcnt Electrodesmentioning
confidence: 99%
“…In order to make the photoresponsive transistors [80] we used the liquid crystalline material tetra(dodecyloxy)hexabenzocoronene (Fig. 12A).…”
Section: Photoresponsive Nanoscale Columnar Transistorsmentioning
confidence: 99%
“…[10] In particular, bromo-and iodo-substituted PFCs are nicely tailored to halogen-bonding-based supramolecular chemistry and behave as robust tectons in crystal engineering. [11] The strength of halogen bonding depends both on the electron deficiency at the donor site and on the Abstract: Halogen bonding effectively co-operates with ion-ion interactions in determining the supramolecular structure of three-component heteromeric crystals comprising of calix [4]arenes, inorganic salts and diiodoperfluoroalkanes. The subtle interplay between these two types of interactions, as well as the influence of the valence of the metal ion, the "size" of the calixarene platform and the length of the perfluorocarbon module on the stoichiometry and overall supramolecular organisation of the ternary supramolecular architectures is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Molecular building blocks are typically organised into higher-order functional structures through the use of noncovalent interactions. New properties arise as a result of this aggregation, [2] which are expressed in a supramolecular function that has found applications in fields ranging from biomimetic structures [3] to molecular electronics [4] and nanoscience. [5] Predicting and designing supramolecular architectures is difficult because of the weakness of the interactions involved.…”
Section: Introductionmentioning
confidence: 99%